2019
DOI: 10.1007/s10980-019-00841-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale mapping of cultural ecosystem services in a socio-ecological landscape: A case study of the international Wadden Sea Region

Abstract: Context The governance of international natural World Heritage sites is extremely challenging. In the search for effective multilevel governance there is a need to identify the community of people which have place attachment to the areas, i.e. 'the community of fans' at local to international levels. Objectives Focusing on the landscape of the international Wadden Sea coastal area in the Netherlands, Germany and Denmark as a case study, we address three key questions: What is the spatial distribution of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
0
19
0
1
Order By: Relevance
“…Thanks to easier international traveling and increasing globalized imaginaries, Bijker and Sijtsma (2017) have demonstrated that citizens-at least in Western countries-have a clear "portfolio of natural places" spanning from the local scale to favourite places at the planetary level. Consequently, citizens from different parts of the world may be attached to the same natural place, constituting what Sijtsma et al (2019) refer to as the "community of fans".…”
Section: Case Study 2: Multi-level Governance and Partaking In Research On The Greenmappermentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to easier international traveling and increasing globalized imaginaries, Bijker and Sijtsma (2017) have demonstrated that citizens-at least in Western countries-have a clear "portfolio of natural places" spanning from the local scale to favourite places at the planetary level. Consequently, citizens from different parts of the world may be attached to the same natural place, constituting what Sijtsma et al (2019) refer to as the "community of fans".…”
Section: Case Study 2: Multi-level Governance and Partaking In Research On The Greenmappermentioning
confidence: 99%
“…Following the previously introduced definition of a digital "community of fans" (Sijtsma et al, 2019), the Greenmapper is designed to explore the reasons behind this connection and how to enable interaction between community members. Crowdsourcing through DPM is, in this case, used to identify these communities and enable their existence (Brown & Kyttä, 2018).…”
Section: Case Study 2: Multi-level Governance and Partaking In Research On The Greenmappermentioning
confidence: 99%
“…Sustainability was originally an ecological term [22]; the term sustainable development, however, has moved beyond ecology into society and the social sciences, and sustainability in contemporary culture is often defined with economic-centric idioms. Although the three tiers of sustainability -economic, environment and social -are all interrelated, the economic tier is a wholly anthropocentric term [24] and thus sustainability is a socio-ecological concept.…”
Section: Introductionmentioning
confidence: 99%
“…'The countless layers of any place come together in specific times and spaces and have bearing on the cultural, economic, and political characteristics, interpretations, and meanings of place' (Graham 2010). PPGIS has developed as an approach to overcome the limitations of 'hard' GIS and introduce 'soft' GIS elements to complement the information support for spatial planning (Kyttä et al 2013;Vich et al 2018;Sijtsma et al 2019). Hard GIS refers to data such as data on land use, job and population densities, and protection and conservation status.…”
Section: Introductionmentioning
confidence: 99%